THE INFLUENCE OF ISLAMIC ATTRIBUTE VALUES AND DESTINATION REPUTATION ON THE REVISIT INTENTION TO HALAL TOURISM DESTINATION OF JAKARTA - Indrani Widjaja, Yunni (Dinasti International Journal of Digital Business Management, 2020)
Based on Indonesian Muslim Travel Index, there are five of the best halal tourism destinations in Indonesia, namely Lombok, Aceh, Riau Islands, Jakarta, and West Sumatra. This research specifically examines Jakarta because of its uniqueness. This study aims to examine the Islamic attribute values and destination reputation toward revisit intention to Jakarta's halal tourism. The research design uses a quantitative approach. The unit of analysis and observation are international Muslim tourists visiting Jakarta. The questionnaire was given to a sample of 100 international Muslim tourists visiting Jakarta. The analytical tool used to test hypotheses is Partial Least Square. The hypothesis testing results indicate that the increase in revisit intention to Jakarta’s halal tourims destination is more dominantly built by destination reputation, followed by Islamic attribute values. The results of this study have implications both theoretically and practicallyIslamic attribute values that include Islamic physical attributes and Islamic non-physical attributes.